RECUPERACIÓN DE RESIDUOS RECICLABLES DEL COLEGIO CALASANZ: UN EJEMPLO DE EDUCACIÓN AMBIENTAL (Biocenosis, 2015)
This article describes the organizational structure and various strategies that have contributed to the optimal development of the Project recovery of recyclable waste at the Colegio Calasanz in order to be an efficient and effective initiative towards achieving environmental education of internal and external members of this community. The project began in 2008 with the participation of teachers, students and parents. Among his achievements is the promotion of moral values such as responsibility, cooperation, respect and friendship stands out, as well as important ecological values such as respect for nature, caring for the environment and solidarity with members of the ecosystem by reducing the environmental impact by our daily actions.
Keywords: Organization; Teams; Work; Leader; Environment